2013
DOI: 10.1080/08911762.2013.804612
|View full text |Cite
|
Sign up to set email alerts
|

Character Portrayal: Examining Gender Roles in Television Commercials Targeted at Children in India and the United States

Abstract: Children's market has been growing steadily not only in the United States but also globally. Advertisers have been targeting this segment heavily in recent years. Given the impact of this segment having increased rapidly in recent years, it is imperative for the advertisers to understand and develop effective advertising messages to reach this segment successfully. One of the essential components of advertisement content includes decisions regarding the gender portrayal of the characters. This study examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Portrayals of boys tend to emphasize masculine gender roles and stereotypically masculine play and toys, whereas portrayals of girls tend to emphasize feminine gender roles and stereotypically feminine play and toys (Cherney and London 2006 ; Kahlenberg and Hein 2010 ). These gendered messages are communicated through various forms of children’s media, including television programming and advertisements (Bakir 2013 ; Bakir and Palan 2013 ; Merskin 2002 ), books (Foster 2016 ; Skinner 2013 ), video games (Miller and Summers 2007 ; Sheldon 2004 ), and print magazines (Spinner et al 2016 ).…”
mentioning
confidence: 99%
“…Portrayals of boys tend to emphasize masculine gender roles and stereotypically masculine play and toys, whereas portrayals of girls tend to emphasize feminine gender roles and stereotypically feminine play and toys (Cherney and London 2006 ; Kahlenberg and Hein 2010 ). These gendered messages are communicated through various forms of children’s media, including television programming and advertisements (Bakir 2013 ; Bakir and Palan 2013 ; Merskin 2002 ), books (Foster 2016 ; Skinner 2013 ), video games (Miller and Summers 2007 ; Sheldon 2004 ), and print magazines (Spinner et al 2016 ).…”
mentioning
confidence: 99%
“…The differences constitute both, an increase in the child audiences and the way the child was portrayed. Bakir (2013) found a strong age difference and gender role stereotypes in advertisements to children. Similarly, in another study by Banik and Dhar (2021), advertisement recall was found to significantly impact purchase decisions.…”
Section: Related Research On Advertising To Childrenmentioning
confidence: 90%
“…For example, the content analysis by Kelly et al (2010) did not collect responses from children directly and considered parents' responses due to limitations. Similarly, in other studies, content analysis is more driven towards gender roles, children's perception towards the product, attitude towards commercials and perception about advertisements (Bakir, 2013;Moore, 2004;Buijzen and Valkenburg, 2002;Shabbir, 2016;Banik and Dhar, 2021). In addition, the role and relationship of the children in the advertisement with the advertised product has not been studied in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, few research articles have examined the gender portrayals targeted at children in India. Bakir (2013) analyzed characters’ self-presentation behaviors on children’s networks in India and the United States using Goffman’s (1976) coding scheme. Relevant elements, such as voice-overs, indicated gender differences, and male voice-overs were used in more than half of the advertisements in both countries.…”
Section: Introductionmentioning
confidence: 99%